Reservoir Modelling and Production Forecasting for Zubair Formation in the Kifl Field - Abdullah, Farah Taha; Al-Jawad, Mohammed Saleh (Iraqi Journal of Science, 2024)
Kifl is a small exploratory field located in central Iraq. This field was not developed, and the reservoir behavior under production conditions was not explored. Building a reservoir model is essential in developing an oil field as it enables the prediction of reservoir performance under different production conditions. This study focused on constructing a reservoir model for the Zubair formation in the Kifl field using available reservoir data and empirical equations to fill in any gaps and then developing the field by suggesting production scenarios. It is important to validate the model to ensure its accuracy before using it in the development plan. The reservoir model was initialized with primary data, such as initial pressure, fluid properties, and datum depth. The model was validated using well-test data of well KF-4 to match the amount of oil and water produced and bottom-hole pressure. Finally, several production scenarios were proposed, involving drilling vertical, horizontal, and single lateral wells, with production gradually increasing in each case. The five cases proposed for field oil production are 3166, 5000, 10000, 15000, and 20000 STB/d, and the production stability was monitored over the proposed development period.